2016
DOI: 10.17140/roj-1-110
|View full text |Cite
|
Sign up to set email alerts
|

On the Destruction of Cancer Cells Using Laser-Induced Shock-Waves: A Review on Experiments and Multiscale Computer Simulations

Abstract: CitationSteinhauser MO. On the destruction of cancer cells using laser-induced shock waves: A review on experiments and multiscale computer simulations. Radiol Open J. 2016 ABSTRACTIn the clinical treatment of solid tumors, besides traditional surgery and chemotherapy, the use of High Intensity Focused Ultrasound (HIFU) has been established as a minimally non-invasive technique for tumor treatment, which is based on coagulative necrosis of cells, induced by conversion of mechanical energy into heat. Another, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…Also the presence of shock waves consequent to the rupture of the trapped cell could be understood from the sudden motion of the surrounding cells in a radially outward direction from the trap point at the moments when the cell under trap gets completely damaged and ejected from the trap (see Video S2). Thermoelastic shockwaves are believed to have potential therapeutic applications by permeabilization of membrane and subsequently controlling transport across it [29,30]. Recently, similar membrane permeabilization phenomena under bipolar electric pulses by generating transient thermoelastic shocks have been experimentally reported [31][32][33] and also described through a full 3-dimensional model by Hu and Joshi [34] which has been found to be in good agreement with experimental observations.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Also the presence of shock waves consequent to the rupture of the trapped cell could be understood from the sudden motion of the surrounding cells in a radially outward direction from the trap point at the moments when the cell under trap gets completely damaged and ejected from the trap (see Video S2). Thermoelastic shockwaves are believed to have potential therapeutic applications by permeabilization of membrane and subsequently controlling transport across it [29,30]. Recently, similar membrane permeabilization phenomena under bipolar electric pulses by generating transient thermoelastic shocks have been experimentally reported [31][32][33] and also described through a full 3-dimensional model by Hu and Joshi [34] which has been found to be in good agreement with experimental observations.…”
Section: Resultssupporting
confidence: 60%
“…We noted that the surrounding RBCs always experience damage on the side that is facing the trap. We believe such damages to surrounding cells may have resulted from the combined action of the heating of the surrounding medium by trap laser and the mechanical effects of shock wave subsequent to the rapid rupture of the trapped cell [29,30]. Also the presence of shock waves consequent to the rupture of the trapped cell could be understood from the sudden motion of the surrounding cells in a radially outward direction from the trap point at the moments when the cell under trap gets completely damaged and ejected from the trap (see Video S2).…”
Section: Resultsmentioning
confidence: 99%
“…High-intensity focused ultrasound (HIFU) has been one of the techniques utilized to induce shock waves often requiring more than one shock wave pulse to elicit quantifiable damage. Interestingly, studies using HIFU have reported similar peak pressures to those generated with lasers ( Steinhauser, 2016 ). However, uncontrolled cavitation by HIFU can lead to difficulty in controlling the amount of shear experienced by cells.…”
Section: Discussionmentioning
confidence: 81%
“…Several laboratories have investigated the effect of shockwaves on cancer cells to determine how it may be utilized for their destruction and sensitization to anti-tumor drugs ( Steinhauser, 2016 ). These studies can shed light on the molecular cascades which may be occurring during a blast-induced TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The objective herein was to investigate the effect of different mechanical characteristics of shock waves on cell viability and identify the governing mechanical parameter or parameters, which is helpful in guiding the tuning of shock waves in medical applications, such as cancer treatment, kidney and gall stones treatments, enhanced drug delivery and diagnostic techniques [24,25]. Laser-induced shock waves were used to investigate the effect on cell viability by varying the shock wave pressure and impulse.…”
Section: Introductionmentioning
confidence: 99%